Enhancing Stabilized Leachate Treatment with C. comosum, E. palaefolius, and E. hyemale in Constructed Wetlands - Imam Nur Nur Rohim; Bimo Tri Goutomo (Universitas Diponegoro, 2026)
Stabilized landfill leachate is challenging to treat because of its high content of refractory organic matter and low biodegradability (BOD/COD ratio <0.16). This study investigated the performance of three ornamental plants, C. comosum, E. palaefolius, and E. hyemale, in laboratory-scale subsurface-flow constructed wetlands for treating stabilized leachate from the Ngipik Landfill, Gresik, Indonesia. The experiments were conducted under batch conditions with a hydraulic retention time (HRT) of 9 days. The treatment efficiency was evaluated based on the removal of BOD, COD, TSS, and TN. E. palaefolius achieved the highest COD and TSS removal efficiencies of 46.92% and 99.36%, respectively. The greatest COD reduction was observed in E. hyemale (63.30%), whereas C. comosum showed the highest TN removal efficiency (93.01%). Despite significant reductions in pollutants, only the TSS concentration in the treated effluents (2-12 mg/L) met the 100 mg/L discharge standard. BOD, COD, and TN levels remained above the regulatory limits. The results indicate that these ornamental plants are suitable for leachate pre-treatment, although longer retention times or additional treatment processes are required to achieve full compliance with environmental standards.